Clinical Circadian Behaviour of Infantile Allergic Rhinitis - Dario Palhares; Lisiane S Ferreira (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Objectives: In a week, not every day the patient with allergic rhinitis will have symptoms; also, in a year, not every month the patient will have complaints. Therefore, the clinical evaluation of allergic rhinitis in children should take in consideration the frequency of symptoms and the circadian cycle.  Methods: forty patients at an outpatient service of general pediatrics who had been diagnosed as presenting active allergic rhinitis were invited to fill up a questionnaire where the symptoms had to be registered at each period of the day, during the following 7 days.  Results: thirty patients completed the study. Each child presented a distinct pattern of weekly behavior, which was seen at the high values of standard deviations. The frequency of the symptoms were significantly reduced between midday and 16:00 hour.  Conclusion: the infantile allergic rhinitis presents a nitid circadian behaviour, being less active around midday. The registration of symptoms during a week revealed that there are patients with almost daily symptoms, but the majority of them present symptoms intermittently, and this information is useful for planning and monitoring the treatment.